Queering Johannesburg: Hillbrow and Soweto as contrasting spaces of Queer Interaction, 1966–1996 - Botes, Jonathan (My University, 2021)
Johannesburg, South Africa’s largest city, has had its own unique history of queer spaces. Beginning with the National Party’s Immorality Amendment Act of 1969 which helped the apartheid state criminalize gay men, and moving through to South Africa’s democratic Constitution which allowed for non-heteronormative sexuality to become legalized, this paper studies how queer people had managed to navigate in Johannesburg by creating their own spaces, as well as covertly using public space in the city. The thesis focuses on Hillbrow, once regarded as the gay centre of Johannesburg, and Soweto, South Africa’s largest township located approximately thirty kilometres outside of Hillbrow. Due to apartheid’s racial segregation, Hillbrow was up until the 1980s a white-only area which gradually deracialized, whilst Soweto has always been a black-area. This research analyses how Hillbrow became a gay centre in the city, how black queer people were able to move in and out of Hillbrow, whilst still creating their own space in Soweto, and how both black and white queer people interacted with each other. By using archives as well as a series of conducted interviews, this research primarily focuses on the everyday interaction of queer people in Hillbrow and Soweto, and how they were able to circumnavigate oppressive laws and create their own spaces in which they were able to express their sexuality. The research also delves into two separate branches of gay liberation politics that were based in Hillbrow, one which focused on a primarily white, male base, and one which formed due to the shortfalls of the prior, which would become inclusive of all races and genders. Drawing personal testimony and archival findings together, this research finds that Johannesburg’s queer population was able to provide vital resources and space in the anti-apartheid movement in order to bring queer people into the discussion regarding equality for all, regardless of sexuality in the African National Congress’ Constitution
A thesis submitted in partial fulfilment of the requirements for the degree of Masters of Arts -Masters in the Department of History, School of Social Sciences, Faculty of Humanities, University of the Witwatersrand, 2021